Earthquake resilience capacity of the Kathmandu Valley, Nepal: a case study of Gairi Gaun - Sapkota, Sanjib; Bhattarai, Tara Nidhi; Khatiwada, Nawa Raj (Journal of Nepal Geological Society, 2011)
Available with full text.